齿轮阻尼环的最佳摩擦力分析 - 孙涛; 刘继岩 (Jixie chuandong)
The gear vibration and noise can be reduced significantly by inserting an appropriate damping ring into the rim of the gear. In order to predict the optimal frictional force between the ring and the gear, a simple dynamic model for the gear damping ring system was presented. The optimal force is determined by developing and solving the differential equations of the dynamic model. The design and application of damping rings can be simplified by using the methods proposed in this paper.